Differences in High School Students' Numeracy Literacy Skills through Problem-Based Learning and Discovery Learning Models - Asri, Mawaddah Nur; Maysarah, Siti (Jurnal Riset Pendidikan Matematika, 2024)
Numeracy literacy skills are essential for students to understand and express quantitative relationships in various real-world contexts. In Indonesia, the literacy level remains low, as indicated by the PISA scores. This study addresses the importance of effective learning models"”Problem-Based Learning (PBL) and Discovery Learning (DL)"”to improve numeracy literacy skills in mathematics, specifically on probability material. The study aims to determine differences in students' numeracy literacy skills when taught using the PBL and DL models. This research uses a quasi-experimental design with a post-test only control group. The study was conducted on 60 students in two experimental groups at SMAN 1 Sei Kepayang, North Sumatra, in the 2024/2025 academic year. Group 1 received the PBL model, while Group 2 applied the DL model. Data were collected through post-tests consisting of essay questions. The findings reveal a significant difference in numeracy literacy skills between the two groups. The average post-test score of the PBL group was 79.13, compared to 63.33 in the DL group. Statistical tests confirmed the significance of this difference. The Problem-Based Learning model is more effective in improving students' numeracy literacy skills compared to the Discovery Learning model, particularly in enhancing problem-solving abilities. These results emphasize the importance of selecting appropriate learning models to foster students' mathematical competencies.